Great Britain in the Commonwealth of Nations - N. A. Stepanova (Vestnik MGIMO-Universiteta)
The article is devoted to an analysis of the role of the Commonwealth of Nations in British history and politics. Having emerged at the end of the XIX c. as an informal association of Britain and dominions within the British Empire it has developed into an independent institute that includes almost all former British territories. Even though nowadays the Commonwealth is a free association of countries and manifests democratic values, this distinctive representation of imperialists stood at its origins, and at times the term itself signified the empire, though in a more progressive, democratic and human form. The author argues that for many decades the main reason for this evolution was British politicians'desire to deter regions from breaking away from within the British sphere of influence. Indeed, the Commonwealth countries belonged to one of the three most important and traditional circles of British political and economic interests, as formulated by W. Churchill, while its importance has been constantly emphasized in numerous election manifestos and government statements. However, with the weakening of Britain and growing independence within the organization, as well as because of contradictions between British national interests and the Commonwealth's founding ideals and principles, Britain has become less and less capable of impacting the organization, and its significance has declined, while some British leaders have even openly sabotaged it. Nevertheless, voices that appeal to reanimate the institution, as well as Britain's role in it, are still heard in the British political arena.